2007
DOI: 10.1167/iovs.06-0410
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Visual Field Sensitivity and Retinal Nerve Fiber Layer Thickness as Measured by Optical Coherence Tomography

Abstract: Evaluation of the structure-function relationship in normal subjects and those with PPG or POAG showed strong curvilinear regression in POAG eyes with PSD >1.9 dB and RNFL AVG thickness below 70 microm, whereas no correlation was detectable above these values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
4
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 28 publications
5
81
4
1
Order By: Relevance
“…It has been shown that analysis of early glaucomatous, healthy individuals, and glaucoma suspect eyes have weaker correlation with VF sensitivity than analyses that include eyes with moderate to severe glaucoma patients, mainly because in healthy and suspect patients, the range of VF loss is narrower. 14,18,28 On the other hand, in the current study, we found that with deterioration of VF, the RNFL thickness tends to be stable despite of changes in VF (Figure 2). Leite et al 18 reported similar findings.…”
Section: Eyecontrasting
confidence: 44%
See 4 more Smart Citations
“…It has been shown that analysis of early glaucomatous, healthy individuals, and glaucoma suspect eyes have weaker correlation with VF sensitivity than analyses that include eyes with moderate to severe glaucoma patients, mainly because in healthy and suspect patients, the range of VF loss is narrower. 14,18,28 On the other hand, in the current study, we found that with deterioration of VF, the RNFL thickness tends to be stable despite of changes in VF (Figure 2). Leite et al 18 reported similar findings.…”
Section: Eyecontrasting
confidence: 44%
“…[2][3][4][5][6]12,14,[16][17][18] However, most of these studies used the Stratus time Correlation of localized glaucomatous VF defects and SD-OCT RNFL thinning H Wu et al domain OCT to measure RNFL thickness. [2][3][4]6,13,14,16,17 Although in two of these studies, SD-OCT was used to evaluated RNFL thickness, 5,18 the structure-function correspondence maps made in those studies correlated VF test points to regions of the ONH. In the present study, we created a modified OCT-based structurefunction map that shows significant correlation between localized areas of VF loss and SD-OCT measurements of RNFL thinning.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations